Encyclopedia of Polymer Science and Technology 2019
DOI: 10.1002/0471440264.pst089.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Crystallization Kinetics

Abstract: Polymer crystallization, like many other phase transitions, occurs through a process of nucleation and growth. Although of fundamental importance, the nucleation step is still poorly understood, nevertheless, though major progress has been achieved in the past decade by using novel analytical tools. Herein, we outline the key experimental data and theories that have been developed to explain these data. A brief look at some more recent approaches is also given. The majority of this article considers the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 240 publications
0
1
0
Order By: Relevance
“…Androsch and Schick reviewed the possible reasons contribute to such bimodal dependence and suggested that as supercooling increases, the significant increase in the nucleation density, accompanied with a change in nucleation mechanism (homogeneous nucleation at high supercooling vs. heterogeneous nucleation at low supercooling), frequently lead to different crystal polymorphs with the mesophase being metastable at high supercooling. [51][52][53] Those factors are presumably the cause for the bimodal dependence of the crystallization rate for PNDI-C3, evidenced by the presence of multiple melting peaks and melting-reorganization process in the subsequent heating scans (Figure 2F). At low supercooling, the formed crystals mainly melt at a peak T m of approximately 104.3 C with a small shoulder-melting peak at lower temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Androsch and Schick reviewed the possible reasons contribute to such bimodal dependence and suggested that as supercooling increases, the significant increase in the nucleation density, accompanied with a change in nucleation mechanism (homogeneous nucleation at high supercooling vs. heterogeneous nucleation at low supercooling), frequently lead to different crystal polymorphs with the mesophase being metastable at high supercooling. [51][52][53] Those factors are presumably the cause for the bimodal dependence of the crystallization rate for PNDI-C3, evidenced by the presence of multiple melting peaks and melting-reorganization process in the subsequent heating scans (Figure 2F). At low supercooling, the formed crystals mainly melt at a peak T m of approximately 104.3 C with a small shoulder-melting peak at lower temperature.…”
Section: Resultsmentioning
confidence: 99%